Self-reported traumatic brain injury in a sample of impulsive violent offenders: neuropsychiatric correlates and possible “dose effects” - Challakere Ramaswamy, Vasudeva Murthy; Butler, Tony; Ton, Bianca; Wilhelm, Kay; Mitchell, Philip B.; Knight, Lee; Greenberg, David; Ellis, Andrew; Allnutt, Stephen; Jones, Jocelyn; Gebski, Val; Carr, Vaughan; et al. (Frontiers in Psychology, 2023)
Background: Traumatic brain injury (TBI) is a major public health problem that may be associated with numerous behavioral problems, including impulsivity, aggression and violence. Rates of selfreported TBI are high within offender populations, but the extent to which TBI is causally implicated in causing illegal behavior is unclear. This study examined the psychological and functional correlates of histories of traumatic brain injury in a sample of impulsive violent offenders.Study participants, all men, had been recruited to participate in a randomized controlled trial of sertraline to reduce recidivism. Study entry criteria were an age of at least 18 years, a documented history of two or more violent offenses and a score of 70 or above on the Barratt Impulsiveness Scale.An extensive list of standardized questionnaires was administered to obtain information on previous TBI and other neuropsychiatric conditions or symptoms.In the sample of 693 men, 66% were aged between 18 and 35 years old, and 55 % gave a history of TBI ('TBI+'). Overall, 55% of study participants reported at least one TBI. High levels of neuropsychiatric symptomatology were reported. In 75% of TBI+ individuals, their most severe TBI (by self-report) was associated with loss of consciousness (LOC) < 30 mins. Compared to TBI-(those without history of TBI) participants, TBI+ individuals were more impulsive (Eysenck Impulsivity), irritable, angry, and reported higher levels of assaultive behavior, depressive symptomology, alcohol use disorder, suicidal ideation, suicide attempts, and lower quality of life. Potential 'dose effects' of TBI severity and frequency in terms of neuropsychiatric symptomatology were identified.Like other studies of offender populations, single and multiple TBIs were very common.The associations of TBI, TBI severity, and TBI frequency (i.e., TBI 'burden') with adverse neuropsychiatric phenomena suggest TBI contributes importantly to offender morbidity but the select nature of the sample and cross-sectional study design constrain the interpretation of these findings.